Genetic and environmental contributions to the link between synaesthesia and neurodevelopmental and psychiatric features : a twin study - Neufeld, Janina; van Leeuwen, Tessa M.; Kuja-Halkola, Ralf; Lundström, Sebastian; Larsson, Henrik; Lichtenstein, Paul; Bölte, Sven; Mataix-Cols, David; Taylor, Mark J. (Translational Psychiatry, 2025)
Synaesthesia is a sensory phenomenon where specific inputs such as written letters or tastes automatically trigger additional sensations (for instance colours). The phenomenon is more common in people on the autism spectrum compared to the general population and seems also to be associated with other neurodevelopmental and psychiatric conditions and features. We assessed the associations between self-reported synaesthesia and eight psychiatric / neurodevelopment features in 18-year-old twins and estimated the genetic and environmental contributions to these associations using classical twin modelling. All of the neurodevelopmental / psychiatric features (related to autism, ADHD, obsessive-compulsive disorder, anxiety, depression, psychotic-like experiences, eating disorders, and (hypo-)mania) correlated positively with self-reported synaesthesia. The strongest association was found with obsessive-compulsive features (r = 0.28). Genetic factors explained more than 50% of most these associations. Environmental factors that are not shared by twins (non-shared environment) influenced the associations to different degrees, while the influence of environmental factors that are shared by twins was estimated to be negligible. Rather than being specifically linked to autism, synaesthesia seems to be associated with a wider range of neurodevelopmental / psychiatric features, and especially obsessive-compulsive features. Genetic factors play a predominant role in most of these associations, suggesting that synaesthesia might share part of its genetic causes with several neurodevelopmental / psychiatric conditions.